Making Time and Space for Art: An Examination of an Artist-in-Residence Within a Postsecondary Art Education Program - Shields, Alison Lea; Percy, Ingrid Mary; Vander Meer-Chassé, Teresa (Canadian Review of Art Education / Revue canadienne d'éducation artistique)

(untitled) (Canadian Society for Education through Art, 2021)
This article examines the process and impact of an artist-in-residence program in Art Education at the University of Victoria. After an open call to artists, contemporary Upper Tanana visual artist, Teresa Vander Meer-Chassé, member of the White River First Nation of Beaver Creek, Yukon and Alaska was selected as the inaugural artist-in-residence. Through research-creation and qualitative methods this research examines the artist’s artistic process and the impact of an artist-in-residence on students’ and faculty’s perception of artistic practice and their experience working with an artist-in-residence within a post-secondary space of learning. Through photographic documentation, reflections and interviews by participants, the article examines ways the artist-in-residence enriched student and faculty learning in a Faculty of Education.